PENGARUH KUALITAS PRODUK DAN KUALITAS PELAYANAN TERHADAP KEPUASAN PELANGGAN PT. INDOMARCO PRISSMATAMA (STUDI KASUS PADA INDOMARET ANCOL 2, JAKARTA) - Tini Juartini (Jurnal Manajemen Bisnis Krisnadwipayana, 2025)
To analyze the influence of product quality and service quality on customer satisfaction at PT. Indomarco Prissmatama. This research is included in the category of causal associative research using a quantitative approach. The population in this study were customers of PT. Indomarco Prissmatama. The sampling technique uses a saturated sample where all members of the population are sampled. The analytical method uses simultaneous and partially linear regression analysis. The research results show that product quality and service quality have a simultaneous and partially effect on customer satisfaction PT. Indomarco Prissmatama.